Metode RGEC dalam Perbandingan Tingkat Kesehatan LKMS di Indonesia Sebelum dan Semasa Pandemi Covid-19 - Suhartono; Selamet (SAFE-Network, 2023)
The existence of a Sharia Financial Institution in recent years has become an alternative financial institution for society which is very important in advancing the real sector. This is because Sharia banks play a role in socializing the practice of profit sharing to avoid the practice of usury (interest). However, in 2019 - 2020 there was a virus that hit all countries in the world which caused the economy to decline. The corona virus (Covid-19) pandemic is still causing ongoing problems. Various sectors have also been affected by this outbreak, including Sharia Microfinance Institutions (IKMS). This research aims to test whether there are differences in the Health Level of Sharia Microfinance Institutions at KSPPS BMT SM NU Kramat Tegal before and during the Covid 19 Pandemic. The population of this research is KSPPS BMT SM NU Kramat. The research was tested using the independent sample t-test. The results of this research show that there are significant differences in NPL, LDR, ROA and CAR at KSPPS BMT SM NU Kramat before and during the Covid 19 pandemic. Meanwhile for GCG and NIM there are no significant differences at KSPPS BMT SM NU Kramat before and during the pandemic covid 19.